2016
DOI: 10.1016/j.bpj.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of Metastasis Modulate the Migratory Response to Cell Contact under Spatial Confinement

Abstract: The breast tumor microenvironment (TMEN) is a unique niche where protein fibers help to promote invasion and metastasis. Cells migrating along these fibers are constantly interacting with each other. How cells respond to these interactions has important implications. Cancer cells that circumnavigate or slide around other cells on protein fibers take a less tortuous path out of the primary tumor; conversely, cells that turn back upon encountering other cells invade less efficiently. The contact response of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 24 publications
6
66
1
Order By: Relevance
“…Pairwise interactions between migrating cells with and without TGFb treatment were imaged and the extent to which interacting cells reversed direction versus sliding past each other was quantified as described in Milano et al (20).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pairwise interactions between migrating cells with and without TGFb treatment were imaged and the extent to which interacting cells reversed direction versus sliding past each other was quantified as described in Milano et al (20).…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that the CFD is an effective metric for quantifying the effects of molecular perturbations on the sliding ability of nontransformed and metastatic breast epithelial cells (20). Cells that slide poorly have a high CFD and require much wider fiberlike tracks to execute moderate levels of sliding; in contrast, cells that slide proficiently have a low CFD and achieve moderate levels of sliding at low fiberlike dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations